Self-assembled albumin nanoparticles induce pyroptosis for photodynamic/photothermal/immuno synergistic therapies in triple-negative breast cancer - Yang, Jianquan; Guo, Wen; Huang, Rong; Bian, Jiaojiao; Zhang, Siqi; Wei, Ting; He, Chuanshi; Hu, Ziyue; Li, Juan; Zhou, Chunyang; Lu, Man (Frontiers in Immunology, 2023)
Triple negative breast cancer (TNBC) is characterized by a high degree of malignancy, early metastasis, limited treatment, and extremely poor prognosis. Immunotherapy, as a new and most promising treatment for cancer, has limited efficacy in TNBC because of the immunosuppressive tumor microenvironment (TME). Inducing pyroptosis and activation of the cyclic guanosine monophosphate-adenosine monophosphate synthase/interferon gene stimulator (cGAS/STING) signaling pathway to upregulate innate immunity has become an emerging strategy for enhancing tumor immunotherapy. In this study, albumin nanospheres were constructed with photosensitizer-IR780 encapsulated in the core and cGAS-STING agonists/H2S producer-ZnS loaded on the shell (named: IR780-ZnS@HSA). In vitro, IR780-ZnS@HSA has the effect of photothermal therapy (PTT) and photodynamic therapy (PDT). Further-more, it can induce pyroptosis in tumor cells through the caspase3-GSDME signaling pathway, and then exhibit robust immungentic cell death (ICD). Meanwhile, IR780-ZnS@HSA can also activate the cGAS-STING signaling pathway. The two pathways synergistically boost immune response. In vivo, IR780-ZnS@HSA + laser can significantly inhibit tumor growth in 4T1 tumor-bearing mice. Meanwhile, the triggered immune response can improve the efficacy of anti-APD-L1 antibody (aPD-L1). In conclusion, IR780-ZnS@HSA, as the novel inducer of pyroptosis, can significantly inhibit tumor growth and improve the efficacy of aPD-L1.